THE INFLUENCE OF WORK ENVIRONMENT AND LEADERSHIP STYLE ON WORK STRESS AND EMPLOYEE PERFORMANCE - Ni Luh Putu Vera Fajarini,; I Wayan Terimajaya,; Ni Luh Sili Antari, (Journal of Innovation Research and Knowledge, 2025)
This study analyzes how work environment and leadership style influence work stress and employee performance. The population of this study consisted of 186 nurses and midwives who were employed in the Inpatient Installation Room of the State General Hospital. The number of subjects included in this study was determined using the Slovin formula, which resulted in a total of 127 people. The research analysis technique employed a multifaceted approach, encompassing several key components. These components included validity and reliability tests, classical assumption tests, and Parth analysis. The findings of the analysis indicated that the work environment and leadership style exerted a negative and significant influence on employee work stress; conversely, the work environment and leadership style demonstrated a positive and significant impact on employee performance. Furthermore, work stress exhibited a negative and significant effect on employee performance, while the work environment exhibited a positive effect on employee performance through employee work stress. The present study sought to ascertain whether work stress could serve as a mediating variable in the relationship between the work environment and employee performance. To this end, an investigation was conducted on the inpatient installation of the State General Hospital. The results of the study indicated that leadership style has a positive effect on employee performance through employee work stress. The present study sought to examine the relationship between leadership style and employee performance in the Inpatient Installation of the State General Hospital. The hypothesis was that work stress would not be a mediating variable in this relationship. The study posits that the leadership of the Inpatient Installation of the State General Hospital can enhance the work environment, refine leadership skills, and alleviate work stress, thereby promoting enhanced employee performance.